1996
DOI: 10.1130/0091-7613(1996)024<0615:belfan>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond EM-1: Lavas from Afanasy-Nikitin Rise and the Crozet Archipelago, Indian Ocean

Abstract: Lavas from Afanasy-Nikitin Rise, possibly the Late Cretaceous product of the Crozet hotspot, cover a wide range of isotopic compositions that includes the lowest (206 Pb/ 204 Pb) t (to 16.77) and Nd (t) (to ؊8) values yet found among oceanic islands or spreading centers worldwide, as well as high (87 Sr/ 86 Sr) t (to 0.7066). In contrast, young basalts from the Crozet Archipelago exhibit a narrow range of variation around Nd ϳ ؉4, 87 Sr/ 86 Sr ϳ 0.7040, and 206 Pb/ 204 Pb ϳ 19.0, closely resembling that of shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 21 publications
(41 reference statements)
6
48
0
1
Order By: Relevance
“…Dashed yellow dots are for Crozet samples without accurate locations from Salters and White [] and Mahoney et al . []. Other data for Crozet samples are from Breton et al .…”
Section: Analytical Resultsmentioning
confidence: 99%
“…Dashed yellow dots are for Crozet samples without accurate locations from Salters and White [] and Mahoney et al . []. Other data for Crozet samples are from Breton et al .…”
Section: Analytical Resultsmentioning
confidence: 99%
“…If the 85°E Ridge is excluded, there are no obvious seamount chains on the track of the Crozet hotspot on the Indian plate (90.0-58.6 Ma) and Antarctic plate (58.6-0 Ma), while the SWIR also had geochemical characters different from those of the Crozet hotspot [35]. Even though errors in the hotspot absolute motion and plate reconstruction were considered, there was no track of the seamount chain consistent with the Crozet hotspot motion in the study area.…”
Section: Origin Of the Crozet Hotspotmentioning
confidence: 96%
“…Kent et al [51] showed that the Crozet hotspot might not have a relationship with the Rajmahal Traps through analysis of Pb and Sr isotopes. From analysis of the Pb isotope, Mahoney et al [35] considered that there were great differences in the geochemical characters of the Crozet hotspot and the Afanasy Nikitin Plateau and did not support the inference that the Afanasy Nikitin Plateau was created by the Crozet hotspot.…”
Section: Origin Of the Crozet Hotspotmentioning
confidence: 97%
See 1 more Smart Citation
“…Curray and Munasinghe (1991) postulated that the Rajmahal Traps in the Bengal Basin, 85 • E Ridge and ANS form the trace of the Crozet hotspot. However, geochemical results of lava samples of ANS do not show affinity to the Crozet hotspot volcanism (Mahoney et al 1996). Though many subsequent researchers favoured the hotspot activity for the emplacement of the ridge (Müller et al 1993;Gopala Rao et al 1997;Subrahmanyam et al 1999;Krishna 2003;Bastia et al 2010;Radhakrishna et al 2010;Michael and Krishna 2011), the source of the hotspot volcanism remains speculative.…”
Section: Introductionmentioning
confidence: 95%